TRIAD1 and HHARI bind to and are activated by distinct neddylated Cullin‐RING ligase complexes. (27th September 2013) - Kelsall, Ian R; Duda, David M; Olszewski, Jennifer L; Hofmann, Kay; Knebel, Axel; Langevin, Frédéric; Wood, Nicola; Wightman, Melanie; Schulman, Brenda A; Alpi, Arno F
<x xml:space="preserve">Abstract</x> RING (Really Interesting New Gene)‐in‐between‐RING (RBR) enzymes are a distinct class of E3 ubiquitin ligases possessing a cluster of three zinc‐binding domains that cooperate to catalyse ubiquitin transfer. The regulation and biological function for most members of the RBR ligases is not known, and all RBR E3s characterized to date are auto‐inhibited for in vitro ubiquitylation. Here, we show that TRIAD1 and HHARI, two members of the Ariadne subfamily ligases, associate with distinct neddylated Cullin‐RING ligase (CRL) complexes. In comparison to the modest E3 ligase activity displayed by isolated TRIAD1 or HHARI, binding of the cognate neddylated CRL to TRIAD1 or HHARI greatly stimulates RBR ligase activity in vitro, as determined by auto‐ubiquitylation, their ability to stimulate dissociation of a thioester‐linked UBCH7∼ubiquitin intermediate, and reactivity with ubiquitin‐vinyl methyl ester. Moreover, genetic evidence shows that RBR ligase activity impacts both the levels and activities of neddylated CRLs in vivo. Cumulatively, our work proposes a conserved mechanism of CRL‐induced Ariadne RBR ligase activation and further suggests a reciprocal role of this special class of RBRs as regulators of distinct CRLs.